Research on network survivability of distance vector routing protocol - WANG Bin1; GUO Yun-fei2; LAN Ju-long2; WU Chun-ming1 (Tongxin xuebao)
The network survivability based on distance vector routing protocol of the network was studied,and the definition of network survivability and its calculation method were given.In order to effectively improve the network survivability of the distance vector routing protocol,A method to measure the authenticity of the update routing message was proposed.Analysis showes that the method can effectively resist false routing messages attacks which is launched by the attack nodes in the network,so it can improve the network survivability of the distance vector routing protocol.